MANAJEMEN PONDOK PESANTREN BERBASIS PENDIDIKAN KARAKTER (Studi Kasus di Pondok Pesantren âAnnuriyyahâ Kaliwining Kecamatan Rambipuji Kabupaten Jember). - Rodliyah, Hj. Siti (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2014)
Abstract: Islamic Boarding School at least have three specials role, (1). As institute Islamic education, (2). Daâwa institute and (3). Institute of society development. Kyai as leader of Islamic Boarding School has an important role in order to upgrading santri quality in the Islamic boarding school with His management to reach vision which expected by leader. Islamic Boarding School represent most effective place for the implementation of character education, because study process in the Islamic Boarding School during 24 hours, santri always in observation of leader and ustadz with specified discipline. Besides that santri civilized and conditioned with positive environment which useful activity for the development potency and personality for themselves.In âAnnuriyyahâ Kaliwining Islamic Boarding School planning base on character education, They tend to barer to all element, proved by planning to every decision making for formulation of vision, mission, target, and planning activity program. Development planning and progress of Islamic Boarding School always entangle inputs from all element in Islamic Boarding School.Â Ø§ÙÙÙØ¸ÙØ§Øª Ø§ÙØ¯Ø¹Ø§ÙØ© ØªØ§Ø³Ø³Ø¤ÙÙ ØØ¯Ø±Ø³Ø© Ø¯Ø§Ø®ÙÙØ© ÙØ§ ÙÙÙ Ø¹Ù Ø«ÙØ§Ø«Ø© Ø£Ø¯ÙØ§Ø± Ø±Ø¦ÙØ³ÙØ© ÙØ«Ù Ø§ÙÙØ¤Ø³Ø³Ø§Øª Ø§ÙØªØ¹ÙÙÙÙØ© Ø§ÙØ¥Ø³ÙØ§ÙÙØ©Â ÙØªÙÙÙØ© Ø§ÙÙØ¬ØªÙØ¹. ÙÙØ§Ù ÙØ±Ø¹Ø§Ø© Ø§ÙØµØ¹ÙØ¯ Ø¯ÙØ±Ø§ ÙØ§ÙØ§ Ø¬Ø¯Ø§ ÙÙ ØªØØ³ÙÙ ÙÙØ¹ÙØ© ÙÙ Ø§ÙØ·ÙØ§Ø¨ ÙÙ ÙØ¯Ø±Ø³Ø© Ø¯Ø§Ø®ÙÙØ© ÙØ³ÙØØ©Â Ø§ÙØ±Ø¤ÙØ© Ø§ÙØªÙ ÙÙ Ø§ÙÙØªÙÙØ¹ ÙÙ ÙØ¨Ù ÙÙØ¯ÙÙ Ø§ÙØ±Ø¹Ø§ÙØ©. ÙØ¯Ø±Ø³Ø© Ø¯Ø§Ø®ÙÙØ© ÙÙ Ø§ÙÙÙØ§Ù Ø§ÙØ£ÙØ«Ø± ÙØ¹Ø§ÙÙØ© ÙÙÙØªØÙØ¹ Ø§ÙØ¥Ø¯Ø§Ø±Ø©Ø ÙÂ Ø¯Ø§Ø¦ÙØ§ ØªØØª ÙÙ Ø¨ÙØ§Ø·ÙØ§Ù ØÙØªÙÙÙØ° Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ·Ø§Ø¨Ø¹Ø ÙØ£Ù Ø¹ÙÙÙØ© Ø§ÙØªØ¹ÙÙ ÙÙ ÙØ¯Ø±Ø³Ø© Ø¯Ø§Ø®ÙÙØ© ØªØ¹ÙÙ ÙÙØ¯Ø© 24 Ø³Ø§Ø¹Ø©Â Ø§ÙÙØ²Ø±ÙØ¹Ø© Ø¨ÙØ§Ø·ÙØ§Ù ØØªÙ ÙØ¶Ø¹ÙØ§. ÙØ¨Ø§ÙØ¥Ø¶Ø§ÙØ© Ø¥ÙÙ Ø°ÙÙ ØªÙÙØ§ ØØ¦Ø§ÙÙÙØ§ÙØ¹ Ø§ÙÙÙØ§Ø¹Ø¯ Ù Ø³ÙØ³ÙØ¥Ø´Ø±Ø§Ù ÙÙØ¯ÙÙ Ø§ÙØ±Ø¹Ø§ÙØ©Ø ÙÙØ´Ø®ØµÙØªÙ. Ø©ÙÙÙØªÙØ§ ØªØ§ÙØ§ÙÙØ¥ÙØ¹ Ø§ÙØ£ÙØ´Ø·Ø© Ø§ÙØ¨ÙØ¦ÙØ© Ø§ÙØ¥ÙØ¬Ø§Ø¨ÙØ© ÙÙ Ø¯Ø§Ø¦ÙØ§ ÙÙÙØ¯ ÙÙ Ø©ÙÙÙÙÙ